1983
DOI: 10.1136/jech.37.4.256
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and bladder cancer: an epidemiological inquiry in West Yorkshire.

Abstract: SUMMARY Results are given of a case-control study on bladder cancer in West Yorkshire. The aim of the study was to assess what risks exist for cigarette smoking in the United Kingdom and also to investigate if a dose response effect was present. The study shows for the first time in the United Kingdom a positive but weak relationship between cigarette smoking and bladder cancer. Close examination of the data with regard to this effect shows that a complex set of relationships result when the quantity smoked an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 16 publications
4
16
0
Order By: Relevance
“…For smokers of blond tobacco, our findings suggest that risk among those who stopped smoking for many years approximates that of nonsmokers, which is consistent with several previous studies (6,14,17,20,21). Findings from other studies, however, indicate that a reduction in risk occurs within the first 2 to 4 years after stopping but that risk either does not continue to decline with increasing time since quitting (3,10,13,19) or continues to decline but does not return to the level of nonsmokers even after 25 years of cessation (12).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For smokers of blond tobacco, our findings suggest that risk among those who stopped smoking for many years approximates that of nonsmokers, which is consistent with several previous studies (6,14,17,20,21). Findings from other studies, however, indicate that a reduction in risk occurs within the first 2 to 4 years after stopping but that risk either does not continue to decline with increasing time since quitting (3,10,13,19) or continues to decline but does not return to the level of nonsmokers even after 25 years of cessation (12).…”
Section: Discussionsupporting
confidence: 92%
“…Studies that have examined the effect of smoking cessation have shown that bladder cancer risk tends to decrease with increasing time since quitting smoking (2,3,6,10,13,14,17,(19)(20)(21). Some have reported that cigarette smokers who inhale deeply may have a greater risk than those who do not (2,5,13,(22)(23)(24), whereas others have found no association between inhalation and bladder cancer risk (3,14,25,26).…”
Section: Introductionmentioning
confidence: 99%
“…The levelling-off of all our dose-response curves is consistent with the findings of others (IARC, 1986). Several features can account for this plateauing, including underestimation of consumption by heavy smokers or, as mentioned by Cartwright et al (1983), it could result from a long-term outcome of competitive diseases related to tobacco consumption, such as lung cancer, leaving a highly resistant group behind. Further, the amounts of tobacco smoked by subjects in our study turn out to be rather variable over time.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor invasion is promoted by factors that alter the tumor microenvironment such as overexpression of cyclooxygenase 2 (COX-2). It has been suggested that etiologic factors, such as cigarette smoking, may be differentially associated with bladder cancer severity 8-13 . Here we examine associations between cigarette smoking and bladder cancer risk taking into account tumor subtypes.…”
Section: Introductionmentioning
confidence: 99%